2010
DOI: 10.1104/pp.110.166876
|View full text |Cite
|
Sign up to set email alerts
|

Low Oleic Acid-Derived Repression of Jasmonic Acid-Inducible Defense Responses Requires the WRKY50 and WRKY51 Proteins    

Abstract: Signaling induced upon a reduction in oleic acid (18:1) levels simultaneously up-regulates salicylic acid (SA)-mediated responses and inhibits jasmonic acid (JA)-inducible defenses, resulting in enhanced resistance to biotrophs but increased susceptibility to necrotrophs. SA and the signaling component Enhanced Disease Susceptibility1 function redundantly in this low-18:1-derived pathway to induce SA signaling but do not function in the repression of JA responses. We show that repression of JA-mediated signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
203
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(209 citation statements)
references
References 59 publications
6
203
0
Order By: Relevance
“…Multiple TGA transcription factor mutants tga235 and tga2356 are blocked in SA-mediated inhibition of JA (Zander et al, 2010;Leon-Reyes et al, 2010b). For WRKY transcription factors, wrky50 and wrky51 mutants do not show SA suppression of JA-mediated PDF1.2 expression (Gao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple TGA transcription factor mutants tga235 and tga2356 are blocked in SA-mediated inhibition of JA (Zander et al, 2010;Leon-Reyes et al, 2010b). For WRKY transcription factors, wrky50 and wrky51 mutants do not show SA suppression of JA-mediated PDF1.2 expression (Gao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the five upregulated WRKYs have all been shown previously to be induced in response to SA treatment, whereas the four that were down-regulated were all undetectable (WRKY12, -14, and -35) or repressed (WRKY44) by SA treatment (69). WRKY38 expression has been linked to the degradation of NPR1 and in combination with WRKY62 is required for systemic acquired resistance (70), and WRKY51 has been shown to mediate SA-dependent repression of JA signaling (71). Another important regulator affecting the antagonism between SA-and JA-mediated signaling is GRX480, which showed a sixfold increase in IAA26-P108H-GFP plants (72).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of a large part of the WKRY transcription factors is SA responsive (Dong et al, 2003), and certain WRKYs have been described as important components in transcriptional regulation of SA-responsive gene expression (Wang et al, 2006;van Verk et al, 2011). A recent report showed that SA-mediated suppression of JA-induced PDF1.2 gene expression was abolished in wrky50 single and wrky50 wrky51 double knockout mutants, indicating that these WRKYs play an important role in SA/JA crosstalk (Gao et al, 2011). Although we did find an overrepresentation of the WRKY binding site (W-box) in promoters of SA/JA crosstalk genes (Figure 4), the PDF1.2 promoter does not contain a W-box element.…”
Section: Mode Of Action Of Sa/ja Signal Interactionmentioning
confidence: 99%
“…Several other molecular players in SA/ JA crosstalk have been identified, including the mitogen-activated protein kinase MPK4 (Petersen et al, 2000), the lipase-like proteins ENHANCED DISEASE SUSCEPTIBILITY1 and PHY-TOALEXIN-DEFICIENT4 (Brodersen et al, 2006), the fatty acid desaturase SUPPRESSOR OF SA INSENSITIVITY2 (Kachroo et al, 2003), glutaredoxin GRX480 (Ndamukong et al, 2007;Zander et al, 2010), and class II TGA and WRKY transcription factors (Li et al, 2004;Mao et al, 2007;Ndamukong et al, 2007;Leon-Reyes et al, 2010a;Zander et al, 2010;Gao et al, 2011). Mutation or ectopic expression of the corresponding genes often have contrasting effects on SA and JA signaling and on resistance against biotrophs and necrotrophs, indicating that these proteins are important regulators of SA/JA crosstalk.…”
Section: Introductionmentioning
confidence: 99%